Analytical modeling of a device for vibration isolation and energy harvesting using simply-supported bi-stable hybrid symmetric laminate. (February 2023) - Li, Ming; Yu, Dong; Li, Yanqi; Liu, Xiaohui; Dai, Fuhong
Abstract: The bi-stable hybrid symmetric laminate (BHSL) has been investigated for vibration isolation and energy harvesting, by taking advantage of its bi-stable characteristic. A device using simply-supported BHSL is proposed to integrate these two functions. This device is called the quasi-zero-stiffness (QZS) vibration isolator with a piezoelectric element (PE). An equivalent theoretical model is developed based on the restoring force-displacement curve of BHSL. The approximate analytical solutions and direct numerical solutions are obtained by the harmonic balance method and the Runge-Kutta method, respectively. Displacement transmissibility is utilized to quantify the vibration isolation performance of this vibration isolator. The influences of the excitation amplitude, the length of BHSL, the width of BHSL and the load resistance are analyzed. The results show that adjusting these parameters can improve the vibration isolation performance and energy harvesting performance. The QZS vibration isolator with PE achieves the goal of higher power density under a low-frequency and low-amplitude excitation and simultaneously has a good vibration isolation performance. Graphical abstract: Image 1 Highlights: Simply-supported bi-stable hybrid symmetric laminate is first used to integrate vibration isolation and energy harvesting. The QZS vibration isolator with PE has the advantage of a lightweight, simple and reliable structure. The equivalent theoretical model is developed to forecast the performances of the QZS vibration isolator with PE. The effects of the excitation amplitude, the length and width of BHSL and the load resistance are considered.